Frequency of Placenta Previa Among Pregnant Patients With Scarred and Unscarred Uterus - Aslam, Sana; Perveen, Saima; Jawad, Arooj; Zubair, Hina; Sabir, Farzana; Razzaq, Hafsa (Biological and Clinical Sciences Research Journal, 2025)
Placenta previa is a serious obstetric condition typically observed during the second and third trimesters of pregnancy. It poses a significant risk for maternal and fetal morbidity and mortality, particularly when associated with prior uterine surgical interventions such as cesarean sections. A history of uterine scarring is a recognized risk factor for placenta previa and its more severe variant, placenta accreta. Objective: To determine the prevalence of placenta previa in pregnant women with and without previous uterine scarring presenting to a tertiary care hospital. Methods: A cross- sectional study was conducted in the Department of Obstetrics & Gynecology at Divisional Headquarter Hospital, Mirpur, from July 1, 2024, to December 31, 2024. A total of 150 pregnant women aged 15–45 years, with gestational age’s ≥28 weeks and singleton pregnancies, were enrolled using a non-probability consecutive sampling technique. Participants were categorized based on the presence or absence of uterine scarring. Women with second-trimester bleeding or primigravida status were excluded. Relevant obstetric history, including parity, gravidity, and gestational age, was documented. Data were analyzed using SPSS version 24. Descriptive statistics were used to summarize demographic and clinical characteristics. Categorical data were presented as frequencies and percentages; continuous data were reported as means ± standard deviations. Results: The mean age of participants was 34.23 ± 12.34 years, with the majority (45.7%) between 26–30 years of age. Regarding gestational age, 13.8% were between 28–32 weeks, 20.83% between 31–35 weeks, and 65.2% between 36–40 weeks. A total of 100 women (66.66%) had previously scarred uteri, while 5 (31.95%) had unscarred uteri. Vaginal delivery history was noted in 46 women. In terms of gravidity, 110 (73.3%) were G2–G4, 35 (23.33%) were G5– G7, and above. Placenta previa was significantly more prevalent among women with a history of uterine scarring. Conclusion: The findings indicate a higher prevalence of placenta previa among women with prior uterine scarring compared to those without. This underscores the need for vigilant prenatal screening and risk stratification in women with a history of cesarean sections or uterine surgeries.